2016
DOI: 10.3945/ajcn.115.112847
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma PUFA concentrations during pregnancy and childhood adiposity: the Generation R Study

Abstract: Lower maternal n-3 PUFA concentrations and higher n-6 PUFA concentrations during pregnancy are associated with higher body fat and abdominal fat in childhood. Additional studies are needed to replicate these observations and to explore the causality, the underlying pathways, and the long-term cardiometabolic consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 50 publications
8
74
2
Order By: Relevance
“…Here, we confirm that those associations have a limited impact over time, since they are absent at age 6 years, as they were at age 4 months [7]. In contrast, previous studies have shown a correlation between maternal PUFA plasma levels during pregnancy and childhood adiposity (by DXA) at age 6 years [2, 4, 5]. Those discrepancies among studies may be partly attributable to differences in the inclusion criteria (i.e., inclusion of children born preterm or small for gestational age) or to differences in PUFA evaluation methods; for example, previous studies have analyzed plasma glycerophospholipids [2, 4, 5], whereas here, we assessed PUFA erythrocyte content, which is considered to be the gold standard biomarker for PUFA consumption, providing information of the previous months’ intake [12].…”
Section: Discussion/conclusionsupporting
confidence: 85%
“…Here, we confirm that those associations have a limited impact over time, since they are absent at age 6 years, as they were at age 4 months [7]. In contrast, previous studies have shown a correlation between maternal PUFA plasma levels during pregnancy and childhood adiposity (by DXA) at age 6 years [2, 4, 5]. Those discrepancies among studies may be partly attributable to differences in the inclusion criteria (i.e., inclusion of children born preterm or small for gestational age) or to differences in PUFA evaluation methods; for example, previous studies have analyzed plasma glycerophospholipids [2, 4, 5], whereas here, we assessed PUFA erythrocyte content, which is considered to be the gold standard biomarker for PUFA consumption, providing information of the previous months’ intake [12].…”
Section: Discussion/conclusionsupporting
confidence: 85%
“…In the Generation R study, similar results were observed with maternal n-3 and n-6 PUFA concentrations in plasma at mid-pregnancy for total body fat mass and preperitoneal fat in infants at 6 years of age (Vidakovic et al, 2016). With regards to the period of lactation, only few studies have investigated the relation between breast milk PUFA concentrations and the development of adiposity in children who were breastfed.…”
Section: Maternal Pufa Intake Obesity and Allergic Diseases 41 Obesitysupporting
confidence: 59%
“…C20:4n-6 acts as precursor for growth-related prostaglandins [48]. In a recent study, lower maternal n-3 polyunsaturated fatty acid (PUFA) concentrations and higher n-6 PUFA concentrations during pregnancy were associated with higher body fat and abdominal fat in children of a large population-based, prospective cohort study [49]. High dietary n-6 fatty acid intakes and low n-3 intakes during pregnancy were reported as a risk indicator of later childhood obesity [50].…”
Section: Discussionmentioning
confidence: 99%